A Nationwide Population-Based Cohort Study: Will Anxiety Disorders Increase Subsequent Cancer Risk? - Liang, Ji-An; Sun, Li-Min; Su, Kuan-Pin; Chang, Shih-Ni; Sung, Fung-Chang; Muo, Chih-Hsin; Kao, Chia-Hung (PLOS ONE, 2012)
Background The aim of this study was to evaluate a possible association between malignancy and anxiety disorders (AD) in Taiwan. Methods We employed data from the National Health Insurance system of Taiwan. The AD cohort contained 24,066 patients with each patient randomly frequency matched according to age and sex with 4 individuals from the general population without AD. Cox's proportional hazard regression analysis was conducted to estimate the influence of AD on the risk of cancer. Results Among patients with AD, the overall risk of developing cancer was only 1% higher than among subjects without AD, and the difference was not significant (hazard ratio [HR] = 1.01, 95% confidence interval [95% CI] = 0.95–1.07). With regard to individual types of cancer, the risk of developing prostate cancer among male patients with AD was significantly higher (HR = 1.32, 95% CI = 1.02–1.71). On the other hand, the risk of cervical cancer among female patients with AD was marginally significantly lower than among female subjects without AD (HR = 0.72, 95% CI = 0.51–1.03). Limitations One major limitation is the lack of information regarding the life style or behavior of patients in the NHI database, such as smoking and alcohol consumption. Conclusions Despite the failure to identify a relationship between AD and the overall risk of cancer, we found that Taiwanese patients with AD had a higher risk of developing prostate cancer and a lower risk of developing cervical cancer.